2021
DOI: 10.1038/s41598-021-82837-6
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen replacement fails to fully revert ovariectomy-induced changes in adipose tissue monoglycerides, diglycerides and cholesteryl esters of rats fed a lard-enriched diet

Abstract: Menopause may be accompanied by abdominal obesity and inflammation, conditions accentuated by high-fat intake, especially of saturated fat (SFA)-rich diets. We investigated the consequences of high-SFA intake on the fatty acid (FA) profile of monoglycerides, diglycerides and cholesteryl esters from retroperitoneal white adipose tissue (RET) of rats with ovariectomy-induced menopause, and the effect of oestradiol replacement. Wistar rats were either ovariectomized (Ovx) or sham operated (Sham) and fed either st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Such results might be attributed to the aberrations in lipid metabolisms of tumor systems. Previous studies have proven that patients with ovarian cancer showed a great increase in MAGs and DAGs but a decrease in triglycerides. As a matter of fact, cancer cells consume abundant nutrients and energy during the intense division process, which places an enormous burden on cellular metabolism. Neural lipids including MAGs and DAGs are uncharged hydrophobic compounds that play a primary role in energy storage, which lead to the increase of MAGs and DAGs in cancer tissues to provide nutrients for the proliferation and differentiation of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Such results might be attributed to the aberrations in lipid metabolisms of tumor systems. Previous studies have proven that patients with ovarian cancer showed a great increase in MAGs and DAGs but a decrease in triglycerides. As a matter of fact, cancer cells consume abundant nutrients and energy during the intense division process, which places an enormous burden on cellular metabolism. Neural lipids including MAGs and DAGs are uncharged hydrophobic compounds that play a primary role in energy storage, which lead to the increase of MAGs and DAGs in cancer tissues to provide nutrients for the proliferation and differentiation of cancer cells.…”
Section: Resultsmentioning
confidence: 99%